Threat analysis for cyber physical system - Ahmed Al-Mhiqani, Mohammed Nasser (2015)
Cyber physical systems are the systems that have an interaction between the computers and the real-world; it has been widely used in many different areas and played a major role in our daily lives, Smart Grid, healthcare, aircrafts, and emergency management are the most areas where CPS applied. However the cyber physical systems currently one of the important hackers‟ target that have a lot of incidents because of the high impacts of these systems, many works have been conducted in CPS but still there are a lack of theories and tools that organizations and researchers can use to understand the natural of the new threats and the impacts that each threat can cause to the physical systems, in this project we will investigate the current threats on CPSs, develop matrices to calculate these threats, and conduct analysis on the collected data using quantitative approach.